Preparation of high piezoelectric and flexible polyvinylidene fluoride nanofibers via lead zirconium titanate doping. Issue 18 (15th December 2020) - Qiao, Xiaojun; Geng, Wenping; Sun, Yao; Yu, Junbin; Chen, Xi; Yang, Yun; Cui, Min; Hou, Xiaojuan; Zeng, Kaiyang; Chou, Xiujian
Abstract: Nanomechanical properties are extremely critical to the applications of flexible electric devices and energy harvester; however, the direct mechanical measurement of composite nanofibers is challenging and rarely explored. In this work, we apply an effective method to obtain the elastic modulus distribution of lead zirconium titanate (PZT)-doped polyvinylidene fluoride (PVDF) nanofibers via bimodal amplitude modulated-frequency modulated scanning probe microscopy (AM-FM SPM). All the samples exhibit obvious piezoelectric properties, and the mechanical properties are clearly enhanced through doping of PZT. Compared with pure PVDF nanofibers, the composite nanofibers with PZT doping show higher elastic modulus which indicates superior stability under the same bending condition. The enhancement of mechanical properties in composite nanofibers via filler doping pave a way to the design of stable and flexible sustainable energy harvesters.